Polityka innowacyjna jako przykład polityki publicznej - Hoffmann, Tomasz (Polityka i Społeczeństwo, 2021)
The article undertakes the issue of innovative policy. It shows that this form of policy is typical of public policies, being characterized by a suitable life cycle and referents. It examines relations between innovative policy and industry, science and the government. One finds that innovative policy is a stimulator of the development of the economy in a given state.